2019
DOI: 10.1021/acsami.9b19809
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl-Group-Wrapped Unsymmetrical Squaraine Dyes for Dye-Sensitized Solar Cells: Branched Alkyl Chains Modulate the Aggregation of Dyes and Charge Recombination Processes

Abstract: Electron transfer processes at the interfaces dictate the factors that improve the photovoltaic parameters, such as open-circuit voltage (V oc ) and short-circuit current (J sc ), of a dye-sensitized solar cell device, besides selection of a set of suitable anode, dye, electrolyte, and cathode materials. An inefficient charge injection process at the dye−TiO 2 interface and charge recombination at the TiO 2 −dye/ electrolyte interface have detrimental effects on improving both J sc and V oc . Hence, tailoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 70 publications
0
83
0
Order By: Relevance
“…Reproduced with permission. [ 5 ] Copyright 2020, American Chemical Society. d‐i) Absorption spectra of SQ4 and SQ22 in DMF; ii) IPCE spectra for DSCs sensitized with SQ4 and SQ22.…”
Section: Squaraine‐based Functional Materials For Photovoltaic Applicmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 5 ] Copyright 2020, American Chemical Society. d‐i) Absorption spectra of SQ4 and SQ22 in DMF; ii) IPCE spectra for DSCs sensitized with SQ4 and SQ22.…”
Section: Squaraine‐based Functional Materials For Photovoltaic Applicmentioning
confidence: 99%
“…Reproduced with permission. [ 5 ] Copyright 2020, American Chemical Society. c) Summary of SQs for photovoltaic and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation of dyes on the TiO 2 surface depends on the length and the location of the flexible chains. A series of unsymmetrical squaraine dyes ( 3 – 8 ) with different alkyl chain lengths at the indoline unit were synthesized to modulate the aggregation of sensitizers on the TiO 2 surface, which resulted in an overall PCE ranging from 3.82% to 6.23% (see Table 1 ) [ 73 ]. In addition, the long chain not only reduces the aggregation, but also prevents the electrolyte from penetrating the dye [ 74 ].…”
Section: Dye Aggregation In Dsscsmentioning
confidence: 99%
“…For a series of squaraine dyes ( 3 – 8 ) (shown in Figure 3 ), although different alkyl chains were introduced to inhibit aggregation, the IPCE responses of the devices fabricated with six dyes were broad, which indicated that both the monomer and aggregated structures contributed to the charge injection process. Also, higher contributions to the IPCE response were observed from the aggregates rather than the monomeric form of the sensitizer [ 73 ].…”
Section: Dye Aggregation In Dsscsmentioning
confidence: 99%